THE EFFECT OF DISBURSED CREDIT, CAPITAL ADEQUACY, AND CASH TURNOVER RATE ON THE PROFITABILITY OF VILLAGE CREDIT INSTITUTIONS (LPD) - Ni Kadek Korita Dewi; I Made Karya Utama (CV. Adiba Aisha Amira, 2025)
This study aims to examine the effect of disbursed credit, capital adequacy, and cash turnover rate on the profitability of Village Credit Institutions (LPD) in Kintamani District, based on the anticipated income theory. The urgency of this study is driven by the high number of unhealthy and non-operational LPDs in Kintamani compared to other districts in Bangli Regency, despite the overall upward trend in net profits and total assets. This discrepancy indicates a potential imbalance between asset growth and financial management efficiency. The study employs secondary data derived from the financial reports of 57 active LPDs in Kintamani from 2021 to 2023, totaling 171 observations, collected using non-probability purposive sampling. Data analysis was conducted using multiple linear regression with SPSS software. The findings show that disbursed credit, capital adequacy, and cash turnover rate have a positive and significant impact on LPD profitability.